Role of Calcination in Sol-Gel Preparation of 3%In-0.1%Gd-TiO2 and Photocatalytic Activity - Li, Hong; Pei, Xiaobei; Chen, Xijuan; Zhang, Wenjie (Current Nanoscience, 2017)
Background: Among some of the widely adopted modification methods, metal ion doping in TiO2 based materials is believed to be helpful to retard recombination of photogenerated electronhole pairs. The combination of indium and gadolinium in synthesizing In-Gd co-doped TiO2 is a new approach. The effects of calcination temperature on characterizations and photocatalytic activity of 3%In-0.1%Gd-TiO2 photocatalyst were investigated. Methods: The In-Gd co-doped 3%In-0.1%Gd-TiO2 were synthesized through a sol-gel process. XRD, SEM, FT-IR/FIR, UV-Vis diffuse reflectance, and N2 adsorption-desorption analyses were measured to the materials. Decoloration of methyl orange was conducted to evaluate the activity of the materials. Results: All the samples are composed of anatase phase TiO2 in tetragonal system despite the difference in calcination temperature, while the crystal cell expands at high temperature. The band gap of the co-doped 3%In-0.1%Gd-TiO2 is lower than the normal band gap of pure TiO2. The average pore size increases and the BET surface area decreases with rising calcination temperature, although the total pore volume is unchanged. The sample calcinated at 400 oC has the strongest activity on photocatalytic degradation of methyl orange. Methyl orange molecules are broken up during photocatalytic degradation process. Conclusion: The rising of calcination temperature leads to enlarging crystallite size and cell expansion of TiO2. A continuous decrease of the adsorbed methyl orange amount can be seen with increasing calcination temperature, while the sample calcinated at 400 oC has the strongest activity on photocatalytic degradation of methyl orange.
Keywords: methyl orange